The extent of Kurdish national identity in the content of the social studies book for grades 4, 5, and 6 in the Kurdistan Region - Muhammed, Prof.Dr. Kawa Ali (Sulaimani Journal for Humanities, 2025)
The purpose of the study was to determine the extent to which the idea of Kurdish national identity is present in the content of social textbooks for grades 4, 5, and 6 of the primary stage in the Kurdistan Region. Therefore, the method of content analysis was used. For this purpose, the analysis tool was prepared following scientific steps. To ensure the accuracy of the tool, the opinions of a group of experts in education and psychology were consulted, and to determine the reliability of the analysis, the researchers analyzed the content at two different times. The final analysis tool consisted of four dimensions (facts, characters, values, and symbols), and the researcher used the 'idea' as the unit of analysis and 'repetition' as the unit of measurement.After analyzing the content of the books, the results showed that the books generally cover the concept of ethnic Kurdish identity to a considerable extent. In this regard, the sixth-grade social studies book ranked first, followed by the fifth-grade book and then the fourth-grade book. Finally, based on the results, some recommendations and suggestions were provided.